Improving Social Science Learning Outcomes of Class V Elementary School Students through the TPACK Approach - Desak Made Dharmawati; Nur Busyra; Ervin Azhar (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThe main problem in this study is the low learning outcomes of fifth grade students in social studies at a private elementary school in East Jakarta, Indonesia. This is because the learning approach used in these schools is still conventional. The purpose of this study was to improve social studies learning outcomes for fifth grade students using the technology pedagogical content knowledge (TPACK) approach. By using classroom action research, this research was conducted in three cycles involving 10 students. Each cycle consists of planning, implementing, acting, observing, and reflecting. Data collection was carried out using a test consisting of a pre-test and post-test. The test results data were then analyzed using descriptive statistics. The results showed that based on the post-test results in cycle I, only 6 students or 60% fulfilled the KKM. In cycle II the percentage of student learning completeness increased to 70% or 7 students fulfilled the KKM. In cycle III, student learning completeness again increased to 82%. Therefore, it can be concluded that the use of the technology pedagogical content knowledge (TPACK) approach in social studies learning is effective in improving student learning outcomes.Keywords: social science learning outcomes, TPACK approach, elementary school students.Â AbstrakMasalah utama dalam penelitian ini adalah rendahnya hasil belajar siswa kelas V IPS di salah satu sekolah dasar swasta di Jakarta Timur, Indonesia. Sebab, pendekatan pembelajaran yang digunakan di sekolah-sekolah tersebut masih konvensional. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar IPS siswa kelas V dengan menggunakan pendekatan technology pedagogi konten pengetahuan (TPACK). Dengan menggunakan penelitian tindakan kelas, penelitian ini dilaksanakan dalam tiga siklus dengan melibatkan 10 siswa. Setiap siklus terdiri dari perencanaan, pelaksanaan, pelaksanaan tindakan, observasi, dan refleksi. Pengumpulan data dilakukan dengan menggunakan tes yang terdiri dari pre-test dan post-test. Data hasil pengujian kemudian dianalisis menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa berdasarkan hasil post-test pada siklus I, hanya 6 siswa atau 60% yang memenuhi KKM. Pada siklus II persentase ketuntasan belajar siswa meningkat menjadi 70% atau 7 siswa yang memenuhi KKM. Pada siklus III ketuntasan belajar siswa kembali meningkat menjadi 82%. Oleh karena itu, dapat disimpulkan bahwa penggunaan pendekatan teknologi pedagogi konten pengetahuan (TPACK) dalam pembelajaran IPS efektif dalam meningkatkan hasil belajar siswa.Kata kunci: hasil belajar IPS, pendekatan TPACK, siswa sekolah dasar.